Effect of Entresto on Clinical Symptoms, Ventricular Remodeling, Rehabilitation, and Hospitalization Rate in Patients with Both Acute Myocardial Infarction and Acute Heart Failure. (16th August 2022) - Wang, Guiping; Liu, Xiaokun; Guo, Zimo; Zhang, Juanjuan; Zuo, Shuping; Sun, Suya; Zhao, Yanan; Zhang, Qi
Abstract : Objective . To determine the influence of Entresto on clinical symptoms, ventricular remodeling (VR), and economic stress of patients with both acute myocardial infarction (AMI) and acute heart failure (AHF). Methods . Totally 120 patients with AMI complicated with AHF admitted to our hospital between January 2017 and August 2019 were enrolled and randomly assigned to an observation group (obs group) and a control group (con group) (each n  = 60). The obs group was treated with Entresto, while the other with angiotensin-converting enzyme inhibitors (ACEI). After treatment, the efficacy on both groups was evaluated, and their cardiac function-associated indexes (left ventricular end-systolic diameter (LVESd), left ventricular end-diastolic dimension (LVEDd), left ventricular ejection fraction (LVEF), VR-associated indexes (interventricular septal thickness (IVST), and left ventricular mass index (LVMI)) were determined and compared before treatment and after 1 month of treatment. Additionally, their NT-pro-BNP, CRP, and TNF- α were tested and compared before and after treatment, and they were also compared in hospitalization time, treatment expense, readmission rate within one year after discharge, and adverse events. Results . After treatment, the obs group showed notably higher efficacy than the con group (P < 0.05 ). Before treatment, the two groups were not greatly different in LVESd, LVEDd, LVEF, IVST, LVMI, NT-pro BNP, CRP, and TNF- α (all P > 0.05 ), while after treatment, these indexes of both groups were improved, but the improvement in the obs group was more notable (P < 0.05 ). Additionally, the hospitalization time, treatment expense, readmission rate one year after discharge, and incidence of adverse events in the obs group were notably lower (all P < 0.05 ). Conclusion . For patients with both AMI and AHF, Entresto can contribute to strong amelioration of their clinical symptoms and prognosis and ventricular reverse-remodeling, with a high safety, so it is worthy of clinical promotion.